The adoption eaudiobook - Meritt, Greg (Tantor Media, 2018)
Their dreams of adoption could haunt their nightmares for eternity . . . Claire Keller would do anything to have a child. Unable to conceive, she's overjoyed when she and her husband bond with the five-year-old girl they adopt. But Claire's hopes for a perfect family shatter when her daughter stands before her covered in blood and prophesying death . . . As the child exhibits more strange supernatural abilities, the frightened Kellers find themselves caught up in a dark plot. Hunted by a shadowy organization hellbent on claiming the girl, the family is forced on the run. But if they can't find shelter from the man obsessed with their daughter's power, their adoption may end up lethally terminated. Can Claire escape a terrifying conspiracy and restore the happy family she's always dreamed of? The Adoption is a standalone science fiction thriller. If you like pulse-pounding action, futuristic tech, and unexpected twists and turns, then you'll love Greg Meritt's suspenseful tale. Buy The Adoption to watch a family battle the unknown today!